WWP2 overexpression inhibits the antitumor effects of doxorubicin in hepatocellular carcinoma. (26th July 2022) - Qin, Yong; Wang, Chao‐Jun; Ye, Hai‐Lin; Ye, Guan‐Xiong; Wang, Shi; Pan, De‐Biao; Wang, Jun; Shen, He‐Juan; Xu, Sheng‐Qian
Abstract: Hepatocellular carcinoma (HCC) is a common liver cancer that accounts for 90% of cases. Doxorubicin exhibits a broad spectrum of antitumor activity and is one of the most active agents in HCC. WW domain‐containing protein 2 (WWP2) is highly expressed in HCC tissues and activates protein kinase B (AKT) signaling pathway to enhance tumor metastasis. However, the role of WWP2 in the glycolysis and antitumor effects of doxorubicin and the epigenetic alterations of WWP2 in HCC remain to be elucidated. The levels of WWP2 and N6‐methyladenosine methyltransferase‐like 3 (METTL3) in clinical samples and cells were investigated. WWP2 were silenced or overexpressed to study the role of WWP2 in regulating cell proliferation, colony formation, and glycolysis. RNA immunoprecipitation was performed to test m 6 A levels. Quantitative reverse‐transcription polymerase chain reaction (RT‐PCR) and Western blot were used to measure mRNA and protein, respectively. WWP2 silencing inhibits cell proliferation, colony formation, and glycolysis, while WWP2 overexpression has the inverse effects via the AKT signaling pathway. Silencing WWP2 enhances doxorubicin's antitumor effect, while WWP2 overexpression suppresses doxorubicin's antitumor effect. Data also support that METTL3 mediates WWP2 m6A modification, and m6A reader, IGF2BP2, binds to the methylated WWP2 to promote the stability of WWP2, leading to upregulation of WWP2. METTL3 mediates WWP2 m6A modification, which can be recognized and bound by IGF2BP2 to increase the stability of WWP2, leading to WWP2 overexpression which inhibits the antitumor effects of doxorubicin through METTL3/WWP2/AKT/glycolysis axis.